Wellness : a novel [large type] - Hill, Nathan, 1975- (Thorndike Press large print top shelf., 2024)
"When Jack and Elizabeth meet as college students in the '90s, the two quickly join forces and hold on tight, each eager to claim a place in Chicago's thriving underground art scene with an appreciative kindred spirit. Fast-forward twenty years to married life, and alongside the challenges of parenting, they encounter cults disguised as mindfulness support groups, polyamorous would-be suitors, Facebook wars, and something called Love Potion Number Nine. For the first time, Jack and Elizabeth struggle to recognize each other, and the no-longer-youthful dreamers are forced to face their demons, from unfulfilled career ambitions to painful childhood memories of their own dysfunctional families. In the process, Jack and Elizabeth must undertake separate, personal excavations, or risk losing the best thing in their lives: each other"--